End-Users’ involvement in the development of web-based learning resources for English Literature - Rashidah Rahamat; Parilah M. Shah; Sharifah Nor Puteh; Rosseni Din; Aidah Abdul Karim (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
Developing teaching and learning materials is one of the ways to improve the pedagogical approaches in today’s diverse classroom. Traditionally, teachers prefer to develop materials using the paper-based concept rather than an ICT-based one. However, with global changes, paper-based materials have gradually lost its charm and the focus is more on the promoting of ICT-based materials. The purpose of this study is to develop and evaluate the usability of a web-based learning resource for the English Literature Component for secondary school students. This article reports on end-user’s perceptions of the quality and importance of the interface of a prototype of the English literature website. A Participatory Design approach which involved four experienced teachers and three students was employed to evaluate the website interface. Questionnaire of Usability Evaluation of Website (QUEW) was adapted for this evaluation process. Results of this formative evaluation process show that almost all aspects categorized as the interface easiness and the website interface displays are considered most important by the end-users. The feedback and comments given by the end-users throughout the process of improving this web-based learning resource helped the researchers to make improvements on the development of the prototype.